Changing the Paradigm of Political Parties Regarding Women's Affirmation Policy: From Quantity to Quality - Sukma, Novira Maharani (Law Research Review Quarterly, 2018)
This article discusses the affirmation policy of women's representation used to increase participation and strengthen women's representation in the political world. This policy has been regulated in the Law on Political Parties and further strengthened in Law Number 7 of 2017 concerning General Elections, which is equal to 30 percent of women's representation in the list of candidates submitted by political parties. But the facts obtained, in the parliamentary seats the proportion of women's representation is still far from ideal. Actually, when we talk about affirmation and nomination policies, it is a final process. The initial process was precisely at the time of regeneration within the party. Political parties play an important role in determining the success of implementing this affirmation policy. Most political parties place women only to fulfill the 30 percent quota that has been determined formally, not used to increase the actualization of women in the political world in Indonesia.